2015
DOI: 10.5603/ep.a2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year estimated risk of bone fracture in women with differentiated thyroid cancer under TSH-suppressive levo-thyroxine therapy

Abstract: Introduction: After thyroidectomy and radioiodine therapy, patients with differentiated thyroid cancer (DTC) are indefinitely treated with levothyroxine (L-T4). Osteoporosis is a debated consequence of hypothyroxinaemia. The aim of this study was to evaluate bone mineral density (BMD) and fracture risk assessed by FRAX in a cohort of DTC women. Material and methods. Seventy-four women with DTC (aged 56.5 ± 9.9 years) treated at the mean age of 51.9 ± 12.0 years were studied. Baseline BMD and FRAX were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Five cross-sectional studies, involving a limited number of patients, have focused on the risk of fracture in patients with DTC treated with TSH suppressive therapy (67,68,69,70,71) (Table 2). Fujiyama et al evaluated 24 postmenopausal women treated with total thyroidectomy for DTC and found no difference in the incidence of vertebral deformity nor in the rate of bone loss between patients and 179 age-matched controls (67).…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 99%
See 1 more Smart Citation
“…Five cross-sectional studies, involving a limited number of patients, have focused on the risk of fracture in patients with DTC treated with TSH suppressive therapy (67,68,69,70,71) (Table 2). Fujiyama et al evaluated 24 postmenopausal women treated with total thyroidectomy for DTC and found no difference in the incidence of vertebral deformity nor in the rate of bone loss between patients and 179 age-matched controls (67).…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 99%
“…In the second study Reverter et al evaluated 33 men (mean age 56 ± 14 years) given TSH suppressive therapy with a median of 15 years and found no difference in the rate of either prevalent or incident (asymptomatic; 18.8 vs 16.7%) vertebral fractures between patients and 33 age-matched controls (69). In the third, Vera et al retrospectively evaluated the rate of prevalent and incident major osteoporotic fractures and hip fractures in 74 women (78% postmenopausal) with DTC with two or more BMD measurements and found no difference compared with a cohort of 120 euthyroid woman comparable for age, menopausal status and BMI, selected among patients evaluated for bone health (70). At variance with these studies, Mazziotti et al evaluated the incidence of radiological vertebral fractures in 179 consecutive women (median age 59 years, all but one postmenopausal) treated with total thyroidectomy for DTC attending to an outpatient endocrine clinic and evaluated for bone health (personal communication from the authors) (71).…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 99%
“…The remaining 8 studies fulfilling all inclusion criteria were reviewed (Table 1). [1011121314151617] Two was from Rochester, USA, 2 from Italy, 1 from Spain, 1 from Netherland, 1 from Japan, and 1 from Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…Vera et al[17] performed simulation study to compare BMD and fracture risk assessed by fracture risk assessment tool (FRAX) between 74 women with DTC (mean age, 51.9±12.0 years) and 120 euthyroid women, who were matched for age, BMI, and menopausal status, at baseline, 3 years and 5.5 years (median). The risks of major osteoporotic fracture and hip fracture were similar in DTC patients and in controls.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have been designed to explore the correlation between bone density changes and LT4 treatment, conflicting findings have been reported (4,5). Most of the reported studies have included small number of patients, and despite this limitation bone density seems to decrease in at least some DTC patients.…”
Section: Introductionmentioning
confidence: 99%